CD-ROM for African research needs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
CD-ROM for African research needs: guidelines for selecting databases edited by Lisbeth Levy 1996 157pp